SUSTAINABILITY FOR STARTUP BUSINESS: THE ROLE OF HUMAN CAPITAL - Mochammad Ridwan; Ina Ratnamiasih; Budi Septiawan (TRIKONOMIKA, 2022)
The development of digital business is currently driving the rapid growth of the startup business. Startups are required to develop their capabilities through human resources, which are important human capital for the business they run. This research was conducted on a sample of startups located in the city of Bandung. The research was conducted for four months with the aim of determining the factors that affect human capital in a startup business and how the influence of human capital on company performance. The research method used is descriptive and quantitative methods with SEM PLS data analysis tools. The results of the study show that the role of human capital is quite large in startup performance. The results of the study also show the influence of all the factors studied, especially HR management and the role of the government as the factors that contribute the most to human capital.